Method for producing paste-like polymerizable and curable composition
The preparation of dental hardening compositions through a two-shaft mixer continuously solves the problem of low efficiency of batch methods, and realizes the production of dental hardening compositions with high viscosity and high strength, which is suitable for the application of dental cutting parts.
Patent Information
- Application Number
- JP2023120163
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-02-05
AI Technical Summary
The prior art When manufacturing dental hardening compositions, batch methods are inefficient and the powder components are dispersed for a long time, making it difficult to meet the needs of efficient production, especially mixed materials for dental cutting parts.
Using a continuous method, a double-shaft mixer is used to mix powdered inorganic powder and liquid monomers. By controlling temperature, rotation speed and shear force, a high viscosity dental hardening composition is prepared to ensure that no curing occurs.
It realizes efficient production of dental hardening compositions, improves production efficiency, ensures high viscosity and high strength hardening effect, and is suitable for the application of dental cutting parts.
Smart Images

Figure 2025017202000005 
Figure 2025017202000006 
Figure 2025017202000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a paste-like polymerizable curable composition. [Background technology]
[0002] Dental curable compositions mainly composed of polymerizable monomers, inorganic fillers, and polymerization initiators, and composite materials (of resin and inorganic filler) such as hybrid resins made of the cured products thereof are widely used as materials for dental prosthetic treatment. For example, the dental curable compositions in an uncured state are used as composite resin restorative materials and dental cements, and the cured products such as hybrid resins are used as materials for the cut parts of dental cutting mill blanks used to manufacture prosthetics such as inlays and crowns using CAD / CAM systems.
[0003] The dental curable composition is usually produced in a batch manner using a device such as a propeller-type agitator, and the inorganic filler is uniformly dispersed in the liquid component that becomes the matrix mainly composed of a polymerizable monomer and a polymerization initiator by applying a relatively low shear stress for a long period of time, regardless of the viscosity of the final paste. In such a batch-type preparation method, in order to improve efficiency, a kneaded product with a high content of powdered filler prepared by adding a powdered component to the liquid component in several batches is first produced as a dilution kneading base material, which is then distributed to the required number of portions, and pigments, etc. and liquid monomers required for viscosity adjustment are added to each distribution and kneaded (see Patent Document 1).
[0004] On the other hand, the cutting part of a dental mill blank for cutting (hereinafter also referred to as "HR mill blank") made of "hybrid resin" (hereinafter sometimes abbreviated as "HR"), which is a composite material in which inorganic filler is dispersed at high density in a resin matrix, is often produced by so-called cast polymerization using a mold (see Patent Documents 2 and 3). For example, in Patent Document 2, the cutting part is produced by injecting a curable composition, which is the raw material of HR, from above into a thermoplastic resin mold using a syringe and then thermally polymerizing it under pressure. In addition, Patent Document 3 describes that a mold made of a cylindrical body having a columnar cavity and an extrusion plate having a flat contact surface that comes into contact with the fluid paste filled inside the mold is used, which is inserted into the columnar cavity so as to be able to move forward and backward, and that a filling tool connected to an injection device is used to fill the extrusion plate from below with the fluid paste, thereby making it possible to fill a paste (curable composition) with low fluidity that is usually difficult to pour into a mold. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2013-014690 A [Patent Document 2] Patent No. 5745198 [Patent Document 3] Patent No. 7266285 Summary of the Invention [Problem to be solved by the invention]
[0006] However, the method disclosed in Patent Document 1 is a so-called batch method, and therefore the productivity is not high, and furthermore, in the process of preparing the diluted kneaded base material, not only is it necessary to add and mix the powder components in several batches, but it is also necessary to perform an operation to adjust the viscosity to the target level, so that dispersion requires time and effort. For this reason, in particular, the production of the dental curable composition that is the raw material for the hybrid resin that is the cutting portion of the dental cutting mill blank can be a bottleneck when the cutting portion is mass-produced by a method such as cast polymerization.
[0007] Therefore, an object of the present invention is to provide a method for efficiently producing the dental hardenable composition by a continuous method. [Means for solving the problem]
[0008] The present invention solves the above-mentioned problems, and a first aspect of the present invention is a method for producing a paste-like polymerizable curable composition that is a viscous fluid, comprising: preparing a powder raw material containing at least one type of inorganic powder and granules, wherein a part of the at least one type of inorganic powder and granules may be contained as an organic-inorganic composite powder and granules constituted by particles composited with a resin; and a liquid raw material containing a polymerizable monomer, wherein at least one of the powder raw material and the liquid raw material contains a thermal polymerization initiator; and kneading the powder raw material and the liquid raw material using a twin-screw kneader, For viscous fluids, (1) The viscosity measured using a rotational viscometer with parallel plates at a temperature of 30°C and a rotation speed of 1 rpm is defined as η1 (unit: Pa s). (2) Viscosity torque measured by a rotational viscometer using parallel plates at a constant temperature and a constant rotation speed: m (rpm): M m (Unit: Pa m 3 ) and shear stress: τ m (Unit: kPa) with the following formula: τ m ={4M m / (3πR 3 )}×10 6 {In the above formula, R represents the radius of the parallel plate (unit: mm).} In torque measurement, a 0.7g viscous fluid sample is compressed to a thickness of 1mm using parallel plates with a radius R of 10mm, and torque measurement is performed at a temperature of 30°C and rotation speeds of 1 rpm and 10 rpm. The torques obtained are M1 and M2, respectively, and the shear stresses calculated by the above formula based on these torques are τ1 and τ 10 The ratio of these shear stresses is τ 10 When / τ1 is the "dilatancy index" of the viscous fluid, the paste-like polymerizable curable composition to be produced has a viscosity η1 of 0.3 to 8 kPa s and a dilatancy index of 2 to 35; The twin-shaft kneader is The barrel has a "connected cylindrical cylinder" formed inside, in which two identical or substantially identical "cylindrical cylinders" arranged in parallel are partially overlapped and integrated, and the cross section perpendicular to the cylindrical axis direction after integration has a shape in which two congruent or substantially congruent circular arcs are butted against each other so as to share a chord, and a pair of screws having the same or substantially the same shape, The pair of screws are rotatably inserted into the two "cylindrical cylinders" constituting the "connected cylindrical cylinder", forming a feed zone (FZ), a kneading zone (KZ) and an expanding zone (EZ), A co-rotating twin-screw kneader in which, while the pair of screws are rotated in the same direction, inside the cylindrical cylinder, a raw material supplied to the FZ is kneaded by applying a shear force in the KZ, and the raw material is extruded to the outside through the EZ, In the kneading, supplying the powder raw material and the liquid raw material to the feed zone (FZ) by adjusting the supply speeds (unit: g / min) of the powder raw material and the liquid raw material so that the amount of each component in the total amount of the powder raw material and the liquid raw material supplied per unit time coincides with a predetermined composition of the paste-like polymerizable curable composition; The barrel temperature in the kneading zone KZ is set to 25°C to 45°C, The inner diameter (diameter) of the cylindrical cylinder in the kneading zone KZ is D (unit: mm), the minimum value of the clearance between the inner wall of the cylindrical cylinder and the screw is c (unit: mm), and pi is the circular constant. Based on these values, the formula: A={(60·c×10 3 ) / (D π)} (unit: Pa): When A is the equipment constant and the rotation speed of the kneading screw during kneading is N (unit: rpm), the value is calculated by the following formula: 10A / η1≦N ≦4500A / η1 The kneading is performed while rotating the kneading screw at a rotation speed N (unit: rpm) that satisfies the condition shown in The present invention relates to a method for producing a paste-like polymerizable curable composition.
[0009] In the manufacturing method of the above embodiment (hereinafter also referred to as "the manufacturing method of the present invention"), it is preferable to include a step of confirming that η1 and dilatancy index of a composition having the same composition as the paste-like polymerizable curable composition are within the above ranges before performing the kneading.
[0010] In addition, it is preferable that the kneading step is carried out using the co-rotating twin-screw kneader having an equipment constant A of 190 to 260.
[0011] It is also preferable to carry out the kneading process so that the residence time (unit: min) obtained by dividing the total mass (unit: g) of the raw materials supplied to the co-rotating twin-screw kneader by the extrusion speed (unit: g / min) of the kneaded product extruded from the co-rotating twin-screw kneader is 3 minutes to 30 minutes.
[0012] Furthermore, it is preferable that the powder raw material contains 20% by mass or more of one or more types of inorganic powder particles having an average primary particle diameter of 0.1 to 1.0 μm measured using a scanning electron microscope, and that the supply rate of the powder raw material and the supply rate of the liquid raw material are controlled so that the amount of the one or more types of inorganic powder particles supplied into the co-rotating twin-screw kneader per unit time is a predetermined amount within a range of 250 to 700 parts by mass when the amount of the polymerizable monomer supplied into the co-rotating twin-screw kneader per unit time is 100 parts by mass. Effect of the Invention
[0013] According to the manufacturing method of the present invention, it is possible to efficiently manufacture a dental curable composition that is the raw material for the hybrid resin that becomes the cutting portion of the dental cutting mill blank, particularly a high-viscosity dental curable composition that has a high inorganic filler content and can give a high-strength cured body (HR), by a continuous method using a continuous kneader such as a twin-screw kneader. [Brief description of the drawings]
[0014] [Figure 1] This figure shows the basic configuration of the screw segments of the apparatus 1 and the apparatuses 3 to 5 used as the co-rotating twin-screw kneaders in the examples. [Diagram 2] This figure shows the basic configuration of the screw segments of the device 2 used as the co-rotating twin-screw kneader in the examples. [Diagram 3] This figure shows the arrangement of kneading discs in the kneading zone of FIGS. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] 1. Overview of the manufacturing method of the present invention It is believed that a paste-like polymerizable hardenable composition that becomes a dental hardenable composition can be more efficiently prepared by kneading a liquid raw material (mainly composed of a monomer) and a powder raw material (mainly composed of an inorganic filler) that are separately prepared at once using a continuous kneader such as a twin-screw kneader, but there are few known examples of preparing dental hardenable compositions by this method. This is believed to be partly because, depending on the mixing ratio of the liquid raw material and the powder raw material, the two do not blend well at the beginning of kneading, and there is a concern that the two raw materials will separate at the beginning of kneading, especially when preparing a low-viscosity dental hardenable composition used for applications in which applicability and fillability into a mold are important.
[0016] By employing the method of filling a mold as described in Patent Document 3, it is possible to fill a high-viscosity dental curable composition capable of producing a high-strength cured body (HR), and since such a dental curable composition has a low monomer content, it is considered that the above-mentioned separation problem is unlikely to occur (due to the small amount of liquid raw material mixed) even when a twin-screw kneader is used. Therefore, the present inventors have investigated the preparation of a high-viscosity paste-like polymerizable curable composition by kneading a liquid raw material and a powder raw material using general conditions for a twin-screw kneader.
[0017] As a result, it was discovered that the paste may solidify (due to polymerization that occurs during kneading) in the twin-screw kneader, that in a system in which such solidification occurs, it is difficult to prevent solidification even by controlling the shear stress applied during kneading, and further that in some cases it is possible to prepare the desired paste-like polymerizable curable composition without causing such solidification.
[0018] As a result of investigations based on such knowledge, it was found that the dilatancy of the paste-like polymerizable curable composition, which is the object of production, affects the solidification, and that it is possible to prepare a paste-like polymerizable curable composition using a twin-screw kneader so long as the dilatancy and viscosity are within specific ranges. It was also found that kneading conditions under which the composition can be prepared efficiently were found, and thus the present invention was completed.
[0019] In other words, the manufacturing method of the present invention is characterized in that, for a high-viscosity paste-like polymerizable curable composition containing a thermal polymerization initiator (viscosity: η1 in the range of 0.3 to 8 kPa s) used as a dental curable composition capable of yielding a high-strength cured body (HR), a range of dilatancy that allows kneading using a twin-screw kneader without causing solidification during kneading has been discovered, and further, kneading conditions that allow the above kneading to be performed efficiently have been discovered.
[0020] In addition, the viscoelastic properties such as viscosity and dilatancy of a paste-like polymerizable curable composition containing a polymerizable monomer, an inorganic filler, and a thermal polymerization initiator are determined by its composition, but the types of substances used as components (raw materials) are various, and it is not possible to immediately determine the degree of viscosity and dilatancy of the composition from the composition. Therefore, when the viscoelastic properties of the paste-like polymerizable curable composition to be manufactured (whether the viscosity and dilatancy of the composition are within a predetermined range or not) are unknown, it is preferable to prepare a paste-like polymerizable curable composition of the same composition in advance by a batch method and confirm the viscosity and dilatancy index of the paste-like polymerizable curable composition. In addition, when the viscoelastic properties can be roughly predicted from the composition, etc., the viscoelastic properties of the obtained paste-like polymerizable curable composition may be measured, and it may be confirmed after the fact that the above conditions are satisfied and that the screw rotation speed satisfies the above conditions.
[0021] The manufacturing method of the present invention is useful as a manufacturing method of a dental hardenable composition, and as the constituent components (raw materials) of the paste-like polymerizable hardenable composition to be manufactured, those used in conventional dental hardenable compositions can be used without any particular restrictions, and the basic structure of the co-rotating twin-screw kneader used is not particularly different from that of the conventionally known kneaders, and an apparatus generally used for extruding plastics, etc., can be used. The present invention will be described in detail below, including these points.
[0022] In this specification, unless otherwise specified, the expression "x to y" using the numerical values x and y means "greater than or equal to x and less than or equal to y." In such an expression, when a unit is assigned only to the numerical value y, the unit is also applied to the numerical value x. In addition, in this specification, the term "(meth)acrylate-based" means both "acrylate-based" and "methacrylate-based."
[0023] 2. Regarding the paste-like polymerizable curable composition which is the product to be manufactured (1) Viscosity and dilatancy The manufacturing method of the present invention aims to efficiently manufacture a paste-like polymerizable curable composition that has been conventionally manufactured by a batch method. For this reason, many of the paste-like polymerizable curable compositions that are the object of manufacture are already known, and their viscoelastic properties can be confirmed in advance. In the present invention, the object of manufacture is a paste-like polymerizable curable composition having viscoelastic properties that are difficult to manufacture using a twin-screw kneader if the manufacturing method of the present invention is not adopted. That is, the object of manufacture is a paste-like polymerizable curable composition having a predetermined composition containing a polymerizable monomer, a filler, and a thermal polymerization initiator, and having a dilatancy index of 2 to 35 and a predetermined value of viscosity: η1 (unit: Pa·s) within the range of 0.3 to 8 kPa·s, as measured by a rotational viscometer using parallel plates under conditions of temperature: 30°C and rotation speed: 1 rpm.
[0024] Here, the viscosity η1 can be determined by adjusting the temperature of the sample stage of a rotational viscometer using parallel plates to 30°C, pressing 0.7 g of a sample (a paste-like polymerizable curable composition to be manufactured that has been prepared in advance by a batch method) between parallel plates of φ20 mm so that the paste has a thickness of 1 mm, leaving the sample to stand for 1 minute, and then measuring the shear rate by scanning at 1 revolution per minute.
[0025] The viscosity of a paste-like polymerizable curable composition containing a filler mainly composed of a polymerizable monomer and inorganic powder and the strength of a cured product of the paste-like polymerizable curable composition depend on the content of the inorganic powder, and the higher the content, the higher the viscosity and the higher the strength of the cured product. In the manufacturing method of the present invention, the viscosity: η1 at 30°C measured by the above method is 0.3 to 8 kPa·s, because a high-strength cured product can be obtained. From the viewpoints of hardness of the cured product and manufacturing efficiency, the viscosity is preferably 0.4 to 6 kPa·s, and more preferably 0.5 to 4 kPa·s.
[0026] The paste-like polymerizable curable composition that is the target of the manufacturing method of the present invention must have a specific dilatancy in addition to the above-mentioned viscosity: η1 being 0.3 to 8 kPa s. Here, dilatancy means a property in which a material is soft and easy to flow when a slow load is applied, but becomes hard and difficult to flow when a strong load is applied, and can be quantitatively expressed using the "dilatancy index" defined below as an index.
[0027] That is, the dilatancy index is the torque (M) (unit: Pa m) measured at different rotation speeds using a rotational viscometer for a sample made of a paste-like composition. 3 ) is defined as the ratio of shear stresses obtained from the rotation speed of 1 rpm: τ1 and the rotation speed of 10 rpm: τ 10 Ratio of: τ 10 This means the value defined by / τ1.
[0028] The torque measured at a rotation speed m (rpm): M m (Unit: Pa m 3 ) and shear stress: τ m (Unit: kPa) is expressed by the following formula: τ m ={4M m / (3πR 3 )}×10 6 {In the above formula, R represents the radius of the parallel plate (unit: mm).} Therefore, the torque measured at 1 rpm is M1 and the torque measured at 10 rpm is M 10 From the above formula, τ1 and τ 10 In the present invention, the temperature of the sample stage of the rotational viscometer is adjusted to 30° C., 0.7 g of a sample (a paste-like polymerizable curable composition previously prepared by a batch method) is pressed against a parallel plate having a diameter of 20 mm so that the paste has a thickness of 1 mm, and the sample is allowed to stand for 1 minute. Then, the shear rate is scanned at 1 (rpm) and 10 (rpm), and the torques at each rotation rate: M1 and M 10 τ is determined based on 10 When the value of the dilatancy index exceeds 1, the material has dilatancy, and the larger the value, the stronger the dilatancy.
[0029] In the production method of the present invention, in order to enable efficient kneading without causing solidification due to polymerization during kneading, the product to be produced has a dilatancy index of 2 to 35. From the viewpoint of the remarkable effect, the dilatancy index of the product to be produced is preferably 3 to 30, and most preferably 4 to 25.
[0030] (2) Raw materials and composition of the paste-like polymerizable hardening composition Next, the components (raw materials) and composition of the paste-like polymerizable curable composition which is the target product to be produced will be described.
[0031] <Polymerizable monomer> The polymerizable monomer, which is a component of the paste-like polymerizable curable composition to be produced, can be appropriately selected from radical polymerizable monomers such as (meth)acrylic compounds, cationic polymerizable monomers such as epoxy compounds and oxetane compounds, etc., but in order to obtain a dental polymerizable curable composition, it is preferable to use a (meth)acrylate-based polymerizable monomer. The (meth)acrylate-based polymerizable monomer may be either a monofunctional polymerizable monomer or a polyfunctional polymerizable monomer, may have an acidic group or a hydroxyl group in the molecule, and may be either an aromatic or aliphatic one. Examples of (meth)acrylate polymerizable monomers that can be suitably used include methyl (meth)acrylate, ethyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, (meth)acrylic acid, N-(meth)acryloylglycine, p-vinylbenzoic acid, 2-(meth)acryloyloxybenzoic acid, 6-(meth)acryloyloxyethylnaphthalene-1,2,6-tricarboxylic acid anhydride, 13-(meth)acryloyloxytridecane-1,1-dicarboxylic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, N-hydroxypropyl (meth)acrylate, 1 ... Examples of the methacryloyloxyethyl (meth)acrylamide include 2,2-bis(methacryloyloxyphenyl)propane, 2,2-bis[(3-methacryloyloxy-2-hydroxypropyloxy)phenyl]propane, ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, 1,6-bis(methacrylethyloxycarbonylamino)trimethylhexane, trimethylolpropane trimethacrylate, pentaerythritol tetramethacrylate, neopentyl glycol dimethacrylate, and 4,4-diphenylmethane diisocyanate.
[0032] A plurality of types of these (meth)acrylate polymerizable monomers may be used in combination as necessary.
[0033] <Filler> The filler used is an inorganic filler and / or an organic-inorganic composite filler. Here, the inorganic filler means a filler consisting of a single type of inorganic powder (aggregate of inorganic particles) (industrially or commercially available as one grade) or a mixture of multiple types of inorganic powder, and the organic-inorganic composite filler means an organic-inorganic composite powder consisting of particles that are a composite of inorganic powder and resin.
[0034] As the material of the inorganic particles contained in the inorganic filler and the organic-inorganic composite filler, amorphous silica, silica-zirconia, silica-titania, silica-titania-barium oxide, silica-titania-zirconia, quartz, alumina, glass, etc. are preferably used. In order to obtain a dental polymerizable curable composition, composite inorganic oxides mainly composed of silica and zirconia or silica and barium oxide, such as silica-zirconia, silica-titania-barium oxide, and silica-titania-zirconia, are preferably used because they have high X-ray contrast. The shape of the inorganic particles is not particularly limited, but when spherical ones are used, the cured body of the obtained paste-like polymerizable curable composition has particularly excellent wear resistance, surface smoothness, and gloss durability.
[0035] Examples of the organic-inorganic composite filler include granular organic-inorganic composite powders obtained by mixing the above-mentioned inorganic powders and polymerizable monomers, polymerizing the mixture, and pulverizing the mixture.
[0036] The inorganic particles may be treated with a surface treatment agent, typically a silane coupling agent, in order to improve the mechanical strength and water resistance.
[0037] In order to obtain a dental polymerizable curable composition, the inorganic powder particles to be the inorganic filler and the inorganic powder particles contained as the organic inorganic filler preferably contain 20 parts by mass or more, more preferably 30 parts by mass or more, of inorganic powder particles having an average primary particle diameter of 0.001 to 3 μm, more preferably 0.1 to 1.0 μm, per 100 parts by mass of the total mass of the filler (including those in the form of organic-inorganic composite filler), from the viewpoints of abrasion resistance, surface smoothness, and gloss durability of the cured product. In addition, the shape of each particle constituting the inorganic powder particles having an average primary particle diameter in the above range is preferably spherical or approximately spherical.
[0038] The average primary particle diameter is determined using a scanning electron microscope. Particles are observed using a scanning electron microscope, and 30 or more particles, preferably 100 or more particles, within a unit visual field are randomly selected, and the primary particle diameter (maximum diameter) of each is measured. The total of the primary particle diameters is divided by the number of selected particles to obtain the average primary particle diameter. Specifically, a photograph of the powder is taken with a scanning electron microscope (manufactured by Philips, "XL-30S") at a magnification of 5,000 to 100,000 times, and the photographed image is processed using image analysis software ("IP-1000PC", product name; manufactured by Asahi Kasei Engineering Corporation), and the number of primary particles observed within a unit visual field of the photograph: n (30 or more, preferably 100 or more) and the particle diameter (maximum diameter): x of each primary particle are determined. i (i represents a natural number from 1 to n, and X i represents the particle diameter of the i-th particle.) is measured, and the formula X i The primary particle diameter (number average) can be calculated by dividing the sum of by n. In addition, the primary particles are said to be spherical or nearly spherical when the number of primary particles observed in the unit field of view of the above photograph is n, and the maximum diameter of each primary particle is the long diameter: L i The diameter perpendicular to the major axis is the minor axis: B i (B i / L i ) divided by n, is 0.6 or more, preferably 0.8 or more.
[0039] The amount of these fillers to be blended may be appropriately determined in consideration of the mechanical properties and viscosity (operability) of the cured product when mixed with the polymerizable monomer according to the purpose of use, but they are generally used in the range of 250 to 700 parts by mass, preferably 300 to 600 parts by mass, per 100 parts by mass of the polymerizable monomer.
[0040] <Thermal polymerization initiator> The thermal polymerization initiator is not particularly limited as long as it has the function of polymerizing and curing the polymerizable monomer by heat, and for example, peroxides such as benzoyl peroxide, p-chlorobenzoyl peroxide, tert-butylperoxy-2-ethylhexanoate, tert-butylperoxydicarbonate, and diisopropylperoxydicarbonate, azo compounds such as azobisisobutyronitrile, boron compounds such as tributylborane, tributylborane partial oxide, sodium tetraphenylborate, sodium tetrakis(p-fluorophenyl)borate, and triethanolamine salt of tetraphenylborate, barbituric acids such as 5-butylbarbituric acid and 1-benzyl-5-phenylbarbituric acid, and sulfinic acid salts such as sodium benzenesulfinate and sodium p-toluenesulfinate can be suitably used. These polymerization initiators may be used alone, or two or more of them may be mixed and used. It is also possible to combine a plurality of initiators with different polymerization methods.
[0041] The amount of the polymerization initiator to be added may be selected according to the purpose, and is usually 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, per 100 parts by mass of the polymerizable monomer.
[0042] <Other additives> The present polymerizable and curable composition may contain other additives, such as a polymerization initiator other than the thermal polymerization initiator, a polymerization inhibitor, an ultraviolet absorber, and a coloring material such as a pigment.
[0043] <Suitable Paste-like Polymerizable Curable Composition> As described above, the viscoelastic properties such as viscosity and dilatancy of a paste-like polymerizable curable composition containing a polymerizable monomer and an inorganic powder or particle are determined by its composition, but it is not possible to immediately determine the degree of viscosity and dilatancy of the composition from the composition. However, a paste-like polymerizable curable composition containing 100 parts by mass of a (meth)acrylic compound-based polymerizable monomer, 250 to 700 parts by mass of inorganic powder particles (including inorganic powder particles contained as an organic-inorganic composite filler), and 0.01 to 10 parts by mass of a thermal polymerization initiator, in which the inorganic powder particles contain 20 mass% or more (based on the total mass of the inorganic powder particles) of one or more kinds of inorganic powder particles having an average primary particle diameter of 0.1 to 1.0 μm measured using a scanning electron microscope, and particularly a paste-like polymerizable curable composition in which the above-mentioned "one or more kinds of inorganic powder particles having an average primary particle diameter of 0.1 to 1.0 μm" are constituted by spherical or nearly spherical inorganic particles, is highly likely to satisfy the conditions of η1=0.3 to 8 kPa·s and dilatancy index=2 to 35. Therefore, such a paste-like polymerizable curable composition is suitable as a production target in the production method of the present invention.
[0044] 3. Manufacturing method of the present invention In the manufacturing method of the present invention, a powder raw material containing at least one type of inorganic powder, where a portion of the at least one type of inorganic powder may be included as an organic-inorganic composite powder constituted by particles composited with a resin, and a liquid raw material containing a polymerizable monomer, in which a thermal polymerization initiator is blended in at least one of the powder raw material and the polymerizable monomer, is prepared (raw material preparation step), and the powder raw material and the liquid raw material are kneaded using a twin-screw kneader (kneading step) to produce the paste-like polymerizable curable composition (the product to be manufactured). Hereinafter, the raw materials, the twin-screw kneader, and the kneading conditions used in the production method of the present invention will be described.
[0045] (1) Raw material preparation process In the raw material preparation step, a powder raw material and a liquid raw material are prepared. Here, the powder raw material is a raw material consisting of a powder containing the filler of the paste-like polymerizable curable composition to be manufactured, that is, the inorganic filler and / or the organic-inorganic composite filler described above, and does not contain a liquid polymerizable monomer in principle, and preferably does not contain any polymerizable monomer at all. In addition, "not containing in principle" here means that it does not contain an amount that impairs the powder properties. On the other hand, the liquid raw material is a liquid raw material containing a polymerizable monomer, and does not contain a filler or a non-soluble material. When the thermal polymerization initiator is insoluble in the polymerizable monomer, it is mixed with the powder raw material, and when it is soluble, it may be mixed with either the powder raw material or the liquid raw material.
[0046] These powder raw materials and liquid raw materials are each supplied to the feed zone (FZ) at a predetermined supply rate (unit: g / min) such that the amount of each component in the total amount of the powder raw materials and the liquid raw materials supplied per unit time is the predetermined composition of the paste-like polymerizable curable composition. Therefore, when the same components are not mixed separately as powder raw materials and liquid raw materials, the quantitative ratio of each component in the powder raw material and the quantitative ratio of each component in the liquid raw material should be the same as the quantitative ratio in the predetermined composition of the paste-like polymerizable curable composition (regardless of the supply rate). For example, when the mass ratio of each component in a predetermined composition of a paste-like polymerizable curable composition is polymerizable monomer:filler:thermal polymerization initiator:pigment (optional component)=α:β:γ:ε, and the powder raw material is composed of a filler and a thermal polymerization initiator, and the liquid raw material is composed of a polymerizable monomer and a pigment, the mass ratio of each component in the powder raw material may be filler:thermal polymerization initiator=β:γ, and the mass ratio of each component in the liquid raw material may be polymerizable monomer:pigment=α:ε. At this time, the supply speed is adjusted so that the mass ratio of the filler to the polymerizable monomer is α:β. On the other hand, when the same component is mixed separately as a powder raw material and a liquid raw material, it is necessary to determine the composition in each raw material in consideration of the supply speed ratio of the powder raw material and the liquid raw material. For this reason, it is preferable not to mix the same component separately as a powder raw material and a liquid raw material.
[0047] (2) Mixing process In the kneading step, the powder raw material and the liquid raw material are kneaded using a twin-screw kneader, but in the production method of the present invention, in order to obtain the effects of the present invention, it is necessary to use a co-rotating twin-screw kneader as the twin-screw kneader and perform kneading under specific kneading conditions. The co-rotating twin-screw kneader and the kneading conditions are described below.
[0048] <Same-rotating twin-shaft kneader> In the manufacturing method of the present invention, a co-rotating twin-screw kneader is used as the twin-screw kneader. By using a co-rotating twin-screw kneader with high self-cleaning properties, solidification does not occur inside the device, and it becomes possible to discharge the desired paste.
[0049] The co-rotating twin-screw kneader used in the manufacturing method of the present invention has a barrel formed therein with a "connected cylindrical cylinder" in which two identical or substantially identical "cylindrical cylinders" arranged in parallel are partially overlapped and integrated, and the cross section perpendicular to the cylindrical axial direction after integration has a shape in which two congruent or substantially congruent circular arcs are butted against each other so as to share a chord, and a pair of screws having the same or substantially the same shape, and one and the other of the pair of screws are rotatably inserted into one and the other of the two "cylindrical cylinders" constituting the "connected cylindrical cylinder", respectively, to form a feed zone: FZ, a kneading zone: KZ, and an extruding zone: EZ, and while the pair of screws are rotating in the same direction, inside the cylindrical cylinder, shear force is applied to the raw material supplied to the FZ by the KZ, and the raw material is extruded to the outside via the EZ.
[0050] In addition, although the terms barrel and cylinder may mean the same thing, in the present invention, the part corresponding to the housing part is referred to as the barrel, and the cylindrical part into which the screw is inserted is referred to as the cylinder. As described above, the cylindrical cylinder has a gourd-shaped cross section formed by joining two cylinders so that two circles of the same diameter overlap each other, and the screws are arranged so that the centers of the two circles coincide with the axes of the two screws, so in this specification, the cylindrical part in which each screw is arranged is referred to as the cylindrical cylinder. Strictly speaking, the cross section perpendicular to the height direction of the cylindrical cylinder is a bisected gourd-shaped cross section (not a perfect circle), so that it is surrounded by a chord connecting two intersections on the circumference and an arc of the non-overlapping part connecting the intersections, but it is treated as a cylinder, and the inner diameter (diameter): D of the cylindrical cylinder means the diameter of the above-mentioned arc part.
[0051] This structure is common for a synchronously rotating twin-shaft kneader, and the screws are rotated by a drive motor of the kneader. The raw materials are supplied using a constant-volume supply device such as a constant-volume supply hopper or a constant-volume pump through a raw material supply hole that communicates with the inside of a cylinder provided in the feed zone (FZ). The raw material supply hole is preferably a circular or angular hole with a diameter of 20 mm or more. The kneaded material is extruded to the outside of the device through a discharge hole that communicates with the tip of the extruding zone (EZ) or a discharge port that communicates from the inside of the cylinder formed at the bottom of the barrel to the outside.
[0052] The arrangement of the zones formed inside the cylindrical cylinder is such that FZ is located at the base end (upstream), EZ is located at the tip end (downstream), and KZ is located between them. In this case, it is acceptable to have multiple FZ-KZ units, for example, an arrangement such as FZ-KZ-FZ-KZ-EZ from the upstream side.
[0053] Furthermore, the pair of screws (sometimes called kneading screws) have the same or substantially the same shape, and each screw has a "feed section" consisting of a feed screw segment that sends the raw material to be kneaded downstream, a "kneading section" consisting of a kneading screw segment including a kneading disk for kneading the raw material sent from the feed section, and an "extrusion section" consisting of an extrusion screw segment that extrudes the kneaded material kneaded in the kneading section from a discharge hole or discharge port to the outside of the device, in this order from the base end to the tip end. The area where the "feed section" is located is the "feed zone: FZ", the area where the "kneading section" is located is the "kneading zone: KZ", and the area where the "extrusion section" is located is the "extruding zone: EZ".
[0054] There are no particular limitations on the screw segment for feeding (sending downstream) used in the feeding section, so long as it can smoothly feed the filler and matrix. A screw with a screw shape is more preferable, since there is less retention in the device.
[0055] The kneading screw segment used in the kneading section can be a flat type kneading disk with a small feeding function and an inclined type kneading disk with an oblique cut so that it can be fed progressively to the downstream part. In particular, the use of a flat type kneading disk is more preferable because the residence time in the kneading section is longer, so that a strong shear stress is applied and the filler can be dispersed in the matrix. In addition, the shape of the kneading disk is more preferable because it has a lens shape with two points where the clearance between the cylinder inner wall surface and the kneading disk is the narrowest, and a rice ball shape with three points where the clearance between the cylinder inner wall surface and the kneading disk is the narrowest, because it has a high shear force and high self-cleaning properties. Among them, the lens shape is more preferable because it is easy to adjust the shear force by changing the configuration angle of the kneading disk. As the angle of the lens shape kneading configuration, the difference in the angle in the clockwise direction before and after the kneading disk can be set to 30° to 150°.
[0056] In addition, the extrusion screw element is not particularly limited as long as it can smoothly send the kneaded material kneaded in the kneading section from the discharge hole or discharge port. When the kneaded material is extruded from the discharge hole communicating with the tip of the EZ, a screw-shaped screw is more preferable because there is less retention in the device, and when the kneaded material is extruded from the discharge port communicating with the outside from the inside of the cylinder formed at the bottom of the barrel, the kneaded material has less sending function and the kneaded material adhering to the screw can be scraped off and discharged, so a flat type kneading disk and an inclined type kneading disk with an oblique cut so that it can be sent in reverse to the downstream part are more preferable.
[0057] The feed screw segment and the kneading screw segment are rotatably inserted into the cylindrical cylinder formed in the barrel, and the pair of screws rotate in the same direction at the same rotation speed, so that the raw material passes between the feed screw segment and the cylinder, and the raw material can be fed. Also, the raw material can be kneaded by applying shear between the kneading screw segment and the cylinder and between the two screws. When the inner diameter of the cylinder (cylindrical cylinder) is small, the production volume per unit time is low and the productivity decreases, and when the inner diameter is large, the production volume per unit time is high but the production loss increases, so it is preferably 8 to 160 (mm), and more preferably 11 to 100 (mm). In addition, the L / D ratio, which is the ratio of the inner diameter D to the length L of the cylinder (cylindrical cylinder), is preferably 7.2 to 40, because a large value increases the residence time in the device, which increases the production loss, and a small value reduces the residence time in the device, which makes it easy for poor dispersion of the filler to occur. Moreover, the minimum clearance c between the cylinder (cylindrical cylinder) and the kneading disc is preferably 0.1 to 2 (mm) at which the shearing force is high, and more preferably 0.15 to 1 (mm).
[0058] Also, the length of the feed screw segment: L f and mixing screw segment length: L k The ratio of L f / L kis preferably 0.1 to 10.
[0059] Ordinary metal materials can be used as the material for the screw and the inner surface of the cylinder. However, since there is wear due to inorganic particles, it is preferable to use a high-strength metal, and it is more preferable to use hard chrome plating, a heat-treated alloy of special steel, ion-nitrided steel, or a cemented carbide alloy mainly composed of tungsten.
[0060] <Mixing conditions> In the kneading step, the powder raw material and the liquid raw material are fed to the feed zone (FZ) arranged at the most upstream side at a predetermined feed rate (unit: g / min) such that the amount of each component in the total amount of the powder raw material and the liquid raw material fed between units becomes the predetermined composition of the paste-like polymerizable curable composition, and kneading is performed. Specifically, the powder raw material is fed using a constant-rate feed hopper, and the liquid raw material is fed using a constant-rate pump. As long as the feed port can be fed at a stable blending ratio without clogging, there is no particular restriction on the order of feeding the powder raw material and the liquid raw material, but since the powder raw material is easier to feed and deliver at a constant rate, and a paste-like polymerizable curable composition with a stable blending ratio can be produced, it is preferable to feed the powder raw material upstream. Furthermore, in order to enable mixing before the powder raw material becomes dense before being mixed with the liquid raw material and becomes difficult to mix, it is more preferable to feed the powder raw material and the liquid raw material at a narrower interval. The supply speed of each raw material is determined based on the residence time (unit: min) obtained by dividing the total mass (unit: g) of the raw materials supplied to the co-rotating twin-screw kneader by the extrusion speed (unit: g / min) of the kneaded product extruded from the co-rotating twin-screw kneader, and the composition of each of the paste-like polymerizable curable composition, the powder raw material, and the liquid raw material. The extrusion speed of the kneaded product depends on the rotation speed of the screw described later, but is preferably 3 to 30 minutes. In addition, when the powder raw material contains 20% by mass or more of a fine inorganic filler having an average primary particle diameter of 0.1 to 1.0 μm measured using a scanning electron microscope, it is preferable to control the supply speed of the powder raw material and the supply speed of the liquid raw material so that the amount of the fine inorganic filler supplied to the co-rotating twin-screw kneader per unit time is a predetermined amount within the range of 250 to 700 parts by mass.
[0061] In the kneading process, the kneading must be performed with the barrel temperature of the kneading zone KZ at 25°C to 45°C. If the temperature is less than 25°C, polymerization inhibition occurs due to condensation, and the polymerization and hardening properties of the kneaded paste decrease, while if the temperature exceeds 45°C, polymerization and hardening start during kneading, resulting in poor kneading. Such temperature control can be performed by water-cooling the outside of the barrel.
[0062] Furthermore, during kneading, the screw rotation speed N (unit: rpm) during kneading is expressed by the following formula: 10A / η1≦N ≦4500A / η1 It is necessary to satisfy the condition shown in
[0063] In the above conditional formula, A is expressed by the following formula: A = {(60·c×10 3 ) / (D π)}(unit: Pa) In the above formula, D means the inner diameter (diameter) (unit: mm) of the cylindrical cylinder in the kneading zone KZ, c means the minimum clearance (unit: mm) between the inner wall of the cylindrical cylinder and the kneading screw in the kneading zone KZ, and π means the circular constant.
[0064] As described above, the above conditions are satisfied by the following formula: Τ={(π·D·N·η) / (60·c)}×10 -3 This is equivalent to the shear stress intensity T (unit: kPa) calculated by setting η = η1 in the above formula being 10 to 4500 kPa. If the shear stress intensity is low, dispersion will be insufficient and a paste with a stable filling rate will not be obtained, whereas if the shear stress intensity is high, the paste will solidify. Therefore, it is preferable that the above T is 20 to 3000 kPa, and particularly 30 to 2500 kPa. When T is 20 to 3000 kPa, the rotation speed N can be calculated by the following formula: 20A / η1≦N ≦3000A / η1 This satisfies the condition shown in When T is 30 to 2500 kPa, the rotation speed N is calculated by the following formula: 30A / η1≦N ≦2500A / η1 This satisfies the condition shown in the following. EXAMPLES
[0065] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0066] 1. About the raw materials The abbreviations and physical properties of the raw materials used in the examples and comparative examples are shown below.
[0067] (A) Polymerizable monomer ·UDMA: 1,6-bis(methacrylethyloxycarbonylamino)trimethylhexane ·TEGGMA: Triethylene glycol dimethacrylate ·NPG: Neopentyl glycol dimethacrylate · bis-GMA: 2,2-bis[(3-methacryloyloxy-2-hydroxypropyloxy)phenyl]propane.
[0068] (B) Polymerization initiator ·BPO: Benzoyl peroxide.
[0069] (C) Fillers (inorganic powders and organic-inorganic composite powders) C1: Organic-inorganic composite filler with an average particle size of 12 μm (containing 83% by mass of γ-methacryloyloxypropyltrimethoxysilane-treated spherical silica zirconia with an average particle size of 0.2 μm. The organic component is a hardened product of M1, which will be described later.) C2 γ-methacryloyloxypropyltrimethoxysilane-treated spherical silica zirconia with an average particle size of 0.2 μm C3 γ-methacryloyloxypropyltrimethoxysilane-treated spherical silica zirconia with an average particle size of 0.4 μm C4 Average particle size 3.0μm amorphous silica zirconia treated with γ-methacryloyloxypropyltrimethoxysilane C5: Irregular silica zirconia with an average particle size of 1.0 μm treated with γ-methacryloyloxypropyltrimethoxysilane.
[0070] The above average particle size was calculated by taking a photograph of the powder at a magnification of 5,000 to 100,000 times using a scanning electron microscope (manufactured by Philips, "XL-30S"), processing the photographed image using image analysis software ("IP-1000PC", product name; manufactured by Asahi Kasei Engineering Corporation), measuring the number of particles observed within a unit field of view of the photograph and the primary particle size (maximum diameter), and calculating the value using the above-mentioned method based on the measured values.
[0071] 2. Liquid and powdered raw materials (1)Liquid raw material In the examples and comparative examples, polymerizable monomer compositions M1 to M3 having the following compositions were used as liquid raw materials. ·M1: UDMA: 70 parts by mass, TEGGMA: 30 parts by mass, and BPO: 1.0 parts by mass ·M2: UDMA: 60 parts by mass, TEGGMA: 20 parts by mass, bis-GMA: 20 parts by mass, and BPO: 1.0 parts by mass ·M3: UDMA: 50 parts by mass, NPG: 50 parts by mass. and BPO: 1.0 parts by mass.
[0072] (2) Powder raw material In the examples and comparative examples, powder compositions F1 to F6 having the following compositions were used as powder raw materials. ·F1: C1:50 parts by mass and C2:50 parts by mass ·F2: C2:30 parts by mass and C4:70 parts by mass ·F3: C2:80 parts by mass and C5:20 parts by mass ·F4: C2:20 parts by mass and C2:80 parts by mass ·F5: C5:100 parts by mass ·F6: C3: 100 parts by mass.
[0073] 3. About the kneading equipment In the examples and comparative examples, the kneading apparatuses used were the co-rotating twin-shaft kneaders 1 to 5. The kneading apparatuses 1 and 3 to 5 are co-rotating twin-shaft kneaders using a pair of screws having the basic configuration of the screw segments shown in Figs. 1 and 3, and the kneading apparatus 2 is a co-rotating twin-shaft kneader using a pair of screws having the basic configuration of the screw segments shown in Figs. 2 and 3. All of them are equipped with a metered supply hopper for supplying powder raw materials and a metered pump for supplying liquid raw materials, and are common in that they are capable of supplying powder raw materials and liquid raw materials to the FZ indicated by the downward arrow in the figure (the powder raw materials are slightly upstream of the liquid raw materials), but the shape of the kneading disk (kneading section element member) of the kneading segment in the screw used, the diameter (mm): D of the cylindrical cylinder, and the minimum clearance (mm): c between the inner wall of the cylindrical cylinder and the kneading disk are as shown in Table 1 below. In addition, "FZ" in Fig. 1 and Fig. 2 represents a feed screw segment, "KZ" represents a kneading screw segment, and "EZ" represents an extrusion screw segment. Also, the notations 30°, 60°, and 90° written under "KZ" in Fig. 1 and Fig. 2 represent the phase difference between the kneading disks (two disks in front and behind) that are adjacently arranged in the "KZ" where these notations are written, as shown in Fig. 3. Also, in Table 1, {(c×10 3 ) / (D π)} (unit: Pa) is also shown.
[0074] [Table 1]
[0075] Example 1 (1) Regarding the paste-like polymerizable and hardenable composition, which is the product to be manufactured The paste-like polymerizable curable composition to be manufactured was prepared separately by a batch method, and its viscoelasticity characteristics were confirmed and its cured body was evaluated. Specifically, the polymerizable monomer composition: M1 and the powder composition: F1 were mixed with 100 parts by mass of M1 and 400 parts by mass of F1 until they were uniform, so that the ratio of the mass of the inorganic particles to the mass of the entire composition of F1 (inorganic filling rate) was 80% by mass, using a planetary mixer, to prepare the paste-like polymerizable curable composition to be manufactured. Next, the viscosity, dilatancy index, and bending strength of the cured body of the prepared composition were measured by the following method.
[0076] (1-1) Viscosity measurement The viscosity η1 (unit: Pa·s) was measured at a temperature of 30°C and a rotation speed of 1 rpm using a Modular Compact Rheometer MCR302 (manufactured by Anton Paar), which is a rotational viscometer using parallel plates, as follows. That is, first, an aluminum disposable sample stage was installed on the main body of the device, and the temperature of the sample stage was adjusted to 30°C. After the temperature of the sample stage stabilized, 0.7 g of the paste-like polymerizable curable composition to be the sample was placed on the sample stage and pressed with a parallel plate (φ20 mm, R=10 mm) connected to the main body of the device so that the thickness of the paste was 1 mm. After leaving it in this state for 1 minute, the shear rate was scanned at 1 revolution per minute using the measurement software RheoCompass (manufactured by Anton Paar), and the paste viscosity η (Pa·s) of the thermally polymerizable curable composition was obtained. As a result, the viscosity η1 was 0.44 kPa·s.
[0077] (1-2) Dilatancy index measurement In the same manner as above, the sample was pressed with a parallel plate (φ20 mm, R=10 mm) and left to stand for 1 minute. Then, using the measurement software RheoCompass (manufactured by Anton Paar), the shear rate was scanned at 1 rotation per minute and 10 rotations per minute. The torque measured at 1 rpm was: M1 (unit: Pa m 3 ) and torque measured at 10 rpm (unit: Pa m 3 ):M 10 From the following formula: τ m ={4M m / (3πR 3 )}×10 6 The corresponding shear stresses (unit: kPa) τ1 and τ 10 Calculate each value and calculate τ 10 The dilatancy index, defined as / τ1, was calculated and found to be 19.0.
[0078] (1-3) Bending strength measurement of hardened body In order to investigate the influence of the kneading method on the hardened body properties, the above-mentioned paste-like polymerizable hardening composition was vacuum degassed, and filled into a rectangular polypropylene mold (14 x 18 x 150 mm) without trapping air bubbles, and the upper surface was smoothed, and then heated and pressurized polymerization was carried out under nitrogen pressure at a pressure of 0.4 MPa, 100°C, and 15 hours using a heated and pressurized polymerization apparatus. The hardened body composition was removed from the mold to obtain a dental cutting blank. A test piece of 1.2 mm x 4.0 mm x 18 mm was cut out from the obtained dental cutting resin material or hardened composition hardened body, and each surface of the test piece was finished with P2000 waterproof abrasive paper. Using the prepared test pieces, a three-point bending test was performed on a 4.0 mm x 18 mm surface using a universal testing machine Autograph (manufactured by Shimadzu Corporation) at room temperature in air, with a support distance of 12.0 mm and a crosshead speed of 1.0 mm / min, and the bending strength (unit: MPa) was calculated using the following formula. Flexural strength = 3FS / (2bh 2 ) In the above formula, F represents the maximum load (unit: N) applied to the test specimen, S represents the distance between the supports (unit: mm), b represents the width of the test specimen measured immediately before the test (unit: mm), and h represents the thickness of the test specimen measured immediately before the test (unit: mm). Ten test pieces were measured, and the average bending strength was taken as the bending strength (reference value) of the batch process preparation, which was 224 MPa.
[0079] (2) Preparation of a paste-like polymerizable curable composition by a continuous kneading method using a co-rotating twin-screw kneader (raw material preparation process and kneading process) A liquid raw material consisting of a polymerizable monomer composition: M1 and a powder raw material consisting of a powder composition: F1 were prepared, and the liquid raw material was supplied at a supply rate of 1.00 (g / min) and the powder raw material was supplied at a supply rate of 4.00 (g / min) using a co-rotating twin-screw kneader, so that the filling rate was 80 mass%, and the screw rotation speed was set to N=100 rpm, and kneading was performed for a residence time in the apparatus of 10 minutes. Kneading was possible (discharged as a paste), and a paste-like polymerizable curable composition was obtained. During kneading, the outside of the barrel of KZ was set to 30°C by water cooling, and kneading was performed after confirming that the temperature had stabilized at 30°C. The following formula was calculated based on the above N and the above values of η1, D, and c: Τ={(π·D·N·η1) / (60·c)}×10 -3 The shear stress intensity T in the twin-screw kneader calculated by the above is 84.9 kPa.
[0080] (3) Evaluation of the paste-like polymerizable and hardenable composition obtained by the continuous kneading method The obtained paste-like polymerizable curable composition was evaluated for its discharged paste properties, viscoelastic properties, dispersion state of inorganic particles, and inorganic filling rate, and the bending strength of the cured product of the paste-like polymerizable curable composition was measured. The specific measurement methods and results are shown below.
[0081] (3-1) Evaluation of properties of discharged paste The properties of the paste obtained by the continuous kneading method were evaluated. The evaluation criteria are shown below. The result was "1 (discharged in a paste state)". 1: Discharge in paste form 2: Discharged in paste form, but the paste is somewhat hard 3: The material is discharged in a paste state, but the paste is hard. 4: The paste does not come out.
[0082] (3-2) Evaluation of viscoelastic properties The viscosity η1 and dilatancy index were measured in the same manner as in (1-1) and (1-2), and these values were equivalent to those in the case of preparation by the batch method.
[0083] (3-3) Evaluation of the dispersion state of inorganic particles The dispersion state of the inorganic particles was evaluated by observing the cured body with a scanning electron microscope (SEM) to check the number of aggregates of the inorganic particles. Specifically, the discharged paste was vacuum degassed, filled and packed into a 10 mm x 12 mm x 14 mm mold, and the upper surface was smoothed. After that, using a heating and pressure polymerization apparatus, heating and pressure polymerization was performed under nitrogen pressure at a pressure of 0.4 MPa, 100°C, and 15 hours. A solid sample of 14 mm x 12 mm x 1 mm was cut out from the removed cured body to prepare a solid sample for scanning SEM measurement. Next, a filler photograph of the above cured body sample was taken with an SEM at a magnification of 500 times, and the number of filler aggregates (those with a diameter larger than the inorganic particles added) was counted when observing the inorganic particles within the field of view, and the number of aggregates of inorganic particles remaining in the paste was evaluated. As a result, no aggregates were observed (the number of aggregates was 0).
[0084] (3-4) Evaluation of inorganic filling rate In order to confirm whether a stable inorganic filling rate had been obtained evenly, the filling rate of three paste samples taken every two minutes from 10 minutes after the start of mixing and discharging was measured, and the difference between the highest filling rate and the lowest filling rate was calculated as the filling rate difference (%), which was 0.1%. The filling rate was measured by using a differential thermal-thermogravimetric simultaneous measurement device "TG / DTA6300" (manufactured by SII NanoTechnology Co., Ltd.) for each discharged paste, according to the following procedure. That is, 0.02 g of the discharged paste was placed in an aluminum pan and used as a sample. The mass loss was measured by heating at a temperature rise rate of 5°C / min, a maximum temperature of 500°C, and a maximum temperature retention time of 90 minutes. The ratio of inorganic particles to organic components was calculated using the obtained mass loss of the polymerizable monomer component and the polymerization initiator (organic component), and the organic component (parts by mass) per 100 parts by mass of inorganic particles was calculated. In addition, 0.02 g of aluminum oxide was used as a reference for the differential thermal-thermogravimetric simultaneous measurement.
[0085] (3-5) Bending strength measurement The obtained paste-like polymerizable curable composition was used to measure the bending strength (reference value) of a product prepared by a continuous method in the same manner as in (1-3). The bending strength (reference value) was 227 MPa, which was equivalent to the bending strength (reference value) of a product prepared by a batch method.
[0086] Examples 2 to 30 and Comparative Examples 1 to 7 (1) Regarding the paste-like polymerizable and hardenable composition, which is the product to be manufactured The products to be manufactured in each of the Examples and Comparative Examples were those in which the type of polymerizable monomer composition, the type of powder composition, and the inorganic filling rate used in Example 1 were changed as shown in Table 2. In addition, paste-like polymerizable curable compositions to be manufactured were prepared by a batch method in the same manner as in Example 1, and the viscosity η1, dilatancy index, and bending strength (reference value) were measured. The results are also shown in Table 2.
[0087] [Table 2]
[0088] (2) Preparation of a paste-like polymerizable curable composition by a continuous kneading method using a co-rotating twin-screw kneader (raw material preparation process and kneading process) The co-rotating twin-screw kneader used in Example 1 was changed to one shown in Table 3, and the type of liquid raw material used was changed to a polymerizable monomer composition and a powder composition corresponding to the target product (shown in Table 2). These were supplied so as to achieve a predetermined inorganic filling rate, and kneading was performed under the kneading conditions shown in Table 3. As a result, kneading was possible (paste could be discharged) except for Comparative Examples 1, 3, 4, 5, and 7.
[0089] [Table 3]
[0090] (3) Evaluation of the paste-like polymerizable and hardenable composition obtained by the continuous kneading method The paste-like polymerizable and curable compositions obtained by the continuous kneading method were evaluated in the same manner as in Example 1. The results are shown in Table 4 together with the results of whether kneading was possible or not.
[0091] [Table 4]
[0092] As shown in Table 4, in Examples 1 to 30 in which the viscosity η1 was 0.3 to 8 kPa s, the shear stress intensity in the twin-screw kneader during kneading was within the range of 10 to 4,500 kPa, and the dilatancy index was 2 to 35, paste-like polymerizable curable compositions equivalent to those prepared by the batch method were obtained.
[0093] In contrast, in Comparative Example 1, which has a composition with a low dilatancy index, Comparative Example 3, which has a composition with a high viscosity, Comparative Example 4, which has a composition with a high shear stress intensity, and Comparative Example 5, which used an apparatus 5 consisting of a reverse feed inclined type kneading screw segment kneading disk, solidification occurred due to the strong dilatancy when the paste was sent downstream, and it was not discharged as a paste.
[0094] In Comparative Example 2, which has a composition with a low dilatancy index, multiple aggregates of inorganic particles were observed to remain in the paste, and stable kneading was not possible due to the large difference in filling rate. Furthermore, in these Comparative Examples, the bending strength was significantly reduced compared to the reference value. This is thought to be due to the fact that multiple aggregates of inorganic particles remained, causing destruction to occur from the aggregates of inorganic particles, resulting in a reduction in bending strength.
[0095] In addition, in Comparative Example 6, in which the barrel temperature was lower than 15°C, moisture was generated when the paste was sent downstream due to rapid cooling, and the moisture was contained in the paste, causing polymerization inhibition, resulting in a bending strength that was significantly lower than the bending strength (reference value) shown in Table 2.
[0096] In addition, in Comparative Example 7, in which the barrel temperature exceeded 45° C., the paste was not sent downstream, and because of the high temperature inside the device, it polymerized and was not discharged as a paste.
Claims
1. A method for producing a paste-like polymerizable curable composition that is a viscous fluid, comprising: preparing a powder raw material containing at least one type of inorganic powder, a portion of which may be contained as an organic-inorganic composite powder constituted by particles composited with a resin; and a liquid raw material containing a polymerizable monomer, the powder raw material and the liquid raw material being at least one of which contains a thermal polymerization initiator; and kneading the powder raw material and the liquid raw material using a twin-screw kneader, the method comprising the steps of: For viscous fluids, (1) The viscosity measured by a rotational viscometer using parallel plates at a temperature of 30° C. and a rotation speed of 1 rpm is defined as η 1 (unit: Pa s), (2) Viscosity torque measured by a rotational viscometer using parallel plates at a constant temperature and a constant rotation speed: m (rpm): M m (Unit: Pa m 3 ) and shear stress: τ m (unit: kPa) and the following formula: t m ={4M m / (3πR 3 )}×10 6 {In the above formula, R represents the radius of the parallel plate (unit: mm).} In torque measurement, a viscous fluid sample weighing 0.7 g is compressed to a thickness of 1 mm using parallel plates with a radius R of 10 mm, and torque measurements are performed at a temperature of 30° C. and rotation speeds of 1 rpm and 10 rpm. The torques obtained are expressed as M 1 and M. 2 The shear stresses calculated based on these torques using the above formula are respectively: τ 1 and τ 10 The ratio of these shear stresses is τ 10 / τ 1 is the "dilatancy index" of the viscous fluid, The η of the paste-like polymerizable curable composition which is the object of production 1 is 0.3 to 8 kPa s and the dilatancy index is 2 to 35; The twin-shaft kneader is The barrel has a "connected cylindrical cylinder" formed therein, in which two identical or substantially identical "cylindrical cylinders" arranged in parallel are partially overlapped and integrated, and the cross section perpendicular to the cylindrical axis direction after integration has a shape in which two congruent or substantially congruent circular arcs are butted against each other so as to share a chord, and a pair of screws having the same or substantially the same shape, The pair of screws are rotatably inserted into the two "cylindrical cylinders" constituting the "connected cylindrical cylinder", forming a feed zone: FZ, a kneading zone: KZ, and an extruding zone: EZ, A co-rotating twin-screw kneader in which, while rotating the pair of screws in the same direction, inside the cylindrical cylinder, a raw material supplied to the FZ is kneaded by applying a shear force in the KZ, and the raw material is extruded to the outside through the EZ, In the kneading, supplying the powder raw material and the liquid raw material to the feed zone (FZ) by adjusting the supply rates (unit: g / min) of these raw materials so that the amounts of each component in the total amount of the powder raw material and the liquid raw material supplied per unit time coincide with a predetermined composition of a paste-like polymerizable curable composition; The barrel temperature in the kneading zone KZ is set to 25° C. to 45° C., The inner diameter (diameter) of the cylindrical cylinder in the kneading zone KZ is D (unit: mm), the minimum value of the clearance between the inner wall of the cylindrical cylinder and the screw is c (unit: mm), and pi is the circular constant. Based on these values, the following equation is calculated: A={(60·c×10 3 ) / (D·π)) (unit: Pa): A is an apparatus constant, and the rotation speed of the kneading screw during kneading is N (unit: rpm), and the value is calculated by the following formula: 10A / W 1 ≦ N ≦ 4500A / W 1 The kneading is performed while rotating the kneading screw at a rotation speed N (unit: rpm) that satisfies the condition shown in 2. The method for producing a paste-like polymerizable curable composition comprising the steps of:
2. Before the kneading, the η of a composition having the same composition as that of the paste-like polymerizable curable composition is 1 and a step of confirming that the dilatancy index is within the above range.
3. The method for producing a paste-like polymerizable curable composition according to claim 1, wherein the kneading step is carried out using the co-rotating twin-screw kneader having an equipment constant A of 190 to 260.
4. 2. The method for producing a paste-like polymerizable curable composition according to claim 1, wherein the kneading step is performed so that a residence time (unit: min) calculated by dividing a total mass (unit: g) of the raw materials supplied to the co-rotating twin-screw kneader by an extrusion speed (unit: g / min) of the kneaded product extruded from the co-rotating twin-screw kneader is 3 to 30 minutes.
5. The powder raw material contains 20% by mass or more of one or more types of inorganic powder or granules having an average primary particle diameter of 0.1 to 1.0 μm as measured using a scanning electron microscope, the supply rate of the powder raw material and the supply rate of the liquid raw material are controlled so that the amount of the one or more types of inorganic powder or particles supplied into the co-rotating twin-screw kneader per unit time is a predetermined amount within a range of 250 to 700 parts by mass when the amount of the polymerizable monomer supplied into the co-rotating twin-screw kneader per unit time is 100 parts by mass; A method for producing the paste-like polymerizable curable composition according to claim 1.
Citation Information
Patent Citations
Novel terpene glucoside and tobacco flavor improver containing the same
JP1982045198A
Method of producing polymerizable composition
JP2013014690A
Manufacturing method and manufacturing device for multi-layered dental processing blanks
JP7266285B2